Development of E-Booklet Based on Case Method on the subject of World War I and II Material for Advanced History Learning at SMA Negeri 18 Palembang - Pama, Citra Ayu Virginia; Safitri, Sani (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
This study aims to determine the effectiveness of the use of e-booklet teaching materials in Advanced History subjects. This study is included in development research using direct observation techniques at the research location, namely SMA Negeri 18 Palembang, then questionnaires were distributed to 40 students in class XI F.8 as research subjects. E-booklets were developed using the Hannafin & Peck development model consisting of the needs analysis phase, design base, and development and implementation phases, each part of which is covered by evaluation and revision. The results of the study indicate that case method-based e-booklets are considered valid and effective for use in history learning. Validation by media, material, and language experts obtained a very valid category (89.7%), one-to-one and small group assessments obtained a very valid category (92.05%), the increase in post-test results was valid (88.8), along with the N-gain results reaching 0.82 which is included in the high or very effective category.